2004
DOI: 10.1002/cphc.200300859
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Spectroscopic Analysis of Nanocluster Formation

Abstract: The importance of small metal clusters in catalysis and the problems in understanding the clustering process in solution are outlined. A new analysis method for UV/Vis spectra is presented and applied to monitor the kinetics of ion reduction and cluster formation in situ. This method, which is based on a combination of two chemometric techniques, takes into account the entire UV/Vis spectrum and offers better interpretation possibilities than the traditional "band-assignment" approach. This is particularly tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 44 publications
1
59
0
Order By: Relevance
“…The wetness impregnation allows for a uniform dispersion of a high weight loading of bivalent Pd 2þ species over the entire surface area of the supported matrices. In situ reduction of the bivalent Pd 2þ species usually results in high active reduced Pd 0 species with a nanocluster structure [14]. We have demonstrated that the Pd 2þ species could be readily converted into the reduced Pd 0 species in alcohol solutions [6,15].…”
Section: Preparation and Characterization Of Porous Chitosan Microsphmentioning
confidence: 97%
“…The wetness impregnation allows for a uniform dispersion of a high weight loading of bivalent Pd 2þ species over the entire surface area of the supported matrices. In situ reduction of the bivalent Pd 2þ species usually results in high active reduced Pd 0 species with a nanocluster structure [14]. We have demonstrated that the Pd 2þ species could be readily converted into the reduced Pd 0 species in alcohol solutions [6,15].…”
Section: Preparation and Characterization Of Porous Chitosan Microsphmentioning
confidence: 97%
“…Among these are metal ions, solvent, reductant, and added stabilizers. This problem has also been addressed [43,44]; the results are presented in Section 4.6.…”
Section: Uv-visible Spectroscopymentioning
confidence: 99%
“…To deal with this problem, Rothenberg et al devised a system, called the "net analyte signal/principle component analysis" (NAS/PCA), in which the spectra of the interfering species are essentially subtracted out of the spectrum, leaving a difference spectrum that they assume is only the spectrum of the nanoclusters [43]. These authors used the NAS/PCA method to study the formation of Pd, Au, and Ag nanoclusters, as well as to study the possibility of forming bimetallic nanoclusters using combinations of those metals.…”
Section: Rothenberg's Uv-visible Study Of Pd Au and Ag Nanocluster mentioning
confidence: 99%
“…9), which is attributed to the nucleation of Pd(0). 55,56 Based on these observations, we can deduce that the reduction of palladium(II) acetate is accelerated by water, which first induces a rapid dissociation to monomer 7 (Scheme 4). Water then exchanges with acetate anions to form palladium(II) hydroxide species, 57 which undergoes transmetalation with Scheme 3 Reaction between Pd 3 (OAc) 6 and water.…”
Section: Stability Of Pd(oac) 2 In the Presence Of Water And Arylboromentioning
confidence: 99%